2021
DOI: 10.1038/s41467-021-23407-2
|View full text |Cite
|
Sign up to set email alerts
|

Switchable stimulated Raman scattering microscopy with photochromic vibrational probes

Abstract: Photochromic probes with reversible fluorescence have revolutionized the fields of single molecule spectroscopy and super-resolution microscopy, but lack sufficient chemical specificity. In contrast, Raman probes with stimulated Raman scattering (SRS) microscopy provides superb chemical resolution for super-multiplexed imaging, but are relatively inert. Here we report vibrational photochromism by engineering alkyne tagged diarylethene to realize photo-switchable SRS imaging. The narrow Raman peak of the alkyne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 45 publications
3
58
0
Order By: Relevance
“…Using SRS imaging, they demonstrated the photoswitching ability in live HeLa cells and also visualized mitochondria diffusion using pulse-chase experiments. 130 Similar to switchable nitrile probes, photoswitchable alkyne probes also have potential application toward super-resolution SRS imaging in the cell silent region. Raman imaging is already used in clinical diagnostics and is being translated from bench to bedside.…”
Section: Discussionmentioning
confidence: 99%
“…Using SRS imaging, they demonstrated the photoswitching ability in live HeLa cells and also visualized mitochondria diffusion using pulse-chase experiments. 130 Similar to switchable nitrile probes, photoswitchable alkyne probes also have potential application toward super-resolution SRS imaging in the cell silent region. Raman imaging is already used in clinical diagnostics and is being translated from bench to bedside.…”
Section: Discussionmentioning
confidence: 99%
“…Combining local vibrational reporters with dyes and fluorescence molecules can simultaneously take advantage of fluorescence and Raman scattering and enhance vibration sensitivity. Recently, Ji et al [201] reported a Raman probe based on alkynetagged diarylethene derivatives and realized photoswitchable SRS imaging. Under UV irradiation, the photo isomerization of these conjugated derivatives produced a frequency red shift in the SRS spectra of the narrow Raman peak of the alkyne group, making the absorption wavelength closer to the SRS pump wavelength.…”
Section: Bioimagingmentioning
confidence: 99%
“…Recently, Ji et al. [ 201 ] reported a Raman probe based on alkyne‐tagged diarylethene derivatives and realized photoswitchable SRS imaging. Under UV irradiation, the photoisomerization of these conjugated derivatives produced a frequency red shift in the SRS spectra of the narrow Raman peak of the alkyne group, making the absorption wavelength closer to the SRS pump wavelength.…”
Section: Changes In the Physical And Chemical Properties Of Daementioning
confidence: 99%
See 1 more Smart Citation
“…Such methods can achieve a few nanometers or sub-nanometer resolution (7)(8)(9). Recently, several super-resolution SRS techniques have been developed (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Nonetheless, it is still challenging to achieve super-resolved Raman imaging without manipulating the samples, and to preserve the temporal resolution without any labeling or additional physical or chemical treatment.…”
mentioning
confidence: 99%